NILAI KARATER FILM NUSSA DAN RARA DALAM PERSEPSI GURU SD NEGERI KECAMATAN BLADO KABUPATEN BATANG - Nur Koidah; Suyitno; Rofian (STKIP Subang, 2023)
The context of this research is to develop the basic potential to have a good heart, think well and behave well to build a multicultural nation. The process of instilling character education in students is not only through formal or non-formal schools, but the instilling of character education can be carried out using different educational media such as mass media, print and electronic media which includes audio, visual and audiovisual media. This research aims to determine the character values ​​in the animated film Nussa and Rara, and through this video it is hoped that it can educate students' characters so that they match the national character. The research was carried out in 28 elementary schools in Blado District, Batang Regency with 28 class III teachers. This research was conducted via WhatsApp chat by sending a video of the Nussa and Rara film episode